1998
DOI: 10.1029/1998jd200015
|View full text |Cite
|
Sign up to set email alerts
|

Intercomparison among chamber, tower, and aircraft net CO2 and energy fluxes measured during the Arctic System Science Land‐Atmosphere‐Ice Interactions (ARCSS‐LAII) Flux Study

Abstract: Abstract. Measurements of net ecosystem CO2 exchange (NEE) and energy balance were made using chamber-, tower-, and aircraft-based measurement techniques in Alaskan arctic tundra ecosystems during the 1994-1995 growing seasons (June-August). One of our objectives was to quantify the interrelationships between the NEE and the energy balance measurements made from different sampling techniques. Qualitative and quantitative intercomparisons revealed that on average the correspondence between the mass and energy f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(78 citation statements)
references
References 40 publications
4
72
1
1
Order By: Relevance
“…This high sensitivity of the CO 2 balance to asymmetric biases of CO 2 uptake and CO 2 release is of major importance as closed chamber CO 2 flux measurements based on linear regression are used for local, regional and global carbon budgets and for the evaluation of the carbon source or sink characteristics of ecosystems or even vegetation zones (e.g. Oechel et al, 1993Oechel et al, , 1998Oechel et al, , 2000.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This high sensitivity of the CO 2 balance to asymmetric biases of CO 2 uptake and CO 2 release is of major importance as closed chamber CO 2 flux measurements based on linear regression are used for local, regional and global carbon budgets and for the evaluation of the carbon source or sink characteristics of ecosystems or even vegetation zones (e.g. Oechel et al, 1993Oechel et al, , 1998Oechel et al, , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Jensen et al, 1996;Xu and Qi, 2001;Pumpanen et al, 2003Pumpanen et al, , 2004Reth et al, 2005;Wang et al, 2006). Also, it is often applied to quantify the net CO 2 exchange between the atmosphere and low-stature canopies typical for tundra (Vourlites et al, 1993;Christensen et al, 1998;Oechel et al, , 1998Oechel et al, , 2000Zamolodchikov and Karelin, 2001), peatlands (Alm et al, , 2007Tuittila et al, 1999;Bubier et al, 2002;Nykänen et al, 2003;Burrows et al, 2004;Drösler, 2005;Laine et al, 2006), forest understorey vegetation (Goulden and Crill, 1997;Heijmans et al, 2004) and agricultural crop stands (Dugas et al, 1997;Wagner et al, 1997;Maljanen et al, 2001;Steduto et al, 2002). Advantageously, the closed-chamber method is relatively low in cost and power consumption, simple to operate and can therefore be used in remote, logistically difficult areas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…So far, there exist very few data sets of its temporal evolution, many of which focus on the CO 2 exchange at the ice-atmosphere interface using either eddy correlation techniques (Baldocchi et al, 1988;Oechel et al, 1998) or chamber techniques (Livingston and Hutchinson (1995) and references therein; see also Schrier-Uijl et al (2010) and Loose et al (2011)). This lack of data is due, to some degree, to the fact that sea ice has for a long time been regarded as an impermeable lid on the ocean (Tison et al, 2002;Bates and Mathis, 2009), despite early works that clearly demonstrated significant gas exchange through sea ice (Gosink et al, 1976).…”
Section: Observationsmentioning
confidence: 99%
“…The vegetation variability is driven by environmental factors that can also have important direct controls on CH 4 emissions (e.g., hydrology [18]), which can further enhance the link between vegetation type and CH 4 flux. Therefore, the spatial heterogeneity of tundra vegetation communities can potentially explain the spatial variability in CH 4 fluxes [24], but can also make it difficult to fully quantify and understand localised differences in CH 4 emissions [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%